Facilities management and its impact on calculating value for money on public-private partnership projects in South Africa - Balram Keeran; Moosa Aadi; Govind Mukesh (en, 2016)
Public private partnerships (PPP)

Value for money--Efficiency and effectiveness

Operational risks

Public sector comparator
amount, and considering the length of the average PPP being extensive any cost estimations come with a large amount of uncertainty, furthermore, when doing a life cycle model, the unavailability of benchmark information to base it on is a challenge in practice
Keywords: University of the Witwatersrand